2022
DOI: 10.1186/s12916-022-02476-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for a causal relationship between type 2 diabetes and peripheral artery disease in both Europeans and East Asians

Abstract: Background Observational studies have revealed that type 2 diabetes (T2D) is associated with an increased risk of peripheral artery disease (PAD). However, whether the two diseases share a genetic basis and whether the relationship is causal remain unclear. It is also unclear as to whether these relationships differ between ethnic groups. Methods By leveraging large-scale genome-wide association study (GWAS) summary statistics of T2D (European-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…Observational studies identi ed signi cant phenotypic correlations between T2D and PAD 33,34 , and indicated patients suffering from T2D with higher risks to developing into PAD. A subsequent study further investigated the shared genetic architecture between T2D and PAD in Europeans and East Asians 12 . Previous work has opened avenues to better understand the genetic heterogeneity underlying T2D and PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies identi ed signi cant phenotypic correlations between T2D and PAD 33,34 , and indicated patients suffering from T2D with higher risks to developing into PAD. A subsequent study further investigated the shared genetic architecture between T2D and PAD in Europeans and East Asians 12 . Previous work has opened avenues to better understand the genetic heterogeneity underlying T2D and PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic blood pressure had strong causal effect among Europeans but showed no evidence among East Asian population, which could indicate an ancestry‐based role for systolic blood pressure in the development of chronic kidney disease. Another Mendelian randomization study by Xuehao et al 52 found consistent causal effect of type 2 diabetes on higher risk of peripheral artery disease among both European and East Asian individuals. Such evidence could suggest that type 2 diabetes is less likely to be affected by ethnic variation in the development of vascular complications, however, multiple studies among different ethnic groups are needed for better judgement and understanding.…”
Section: Evidence From Studies Of Non‐europeansmentioning
confidence: 90%
“…A number of trans-ethnic MR analyses has been published, predominantly featured in applied research articles [26][27][28] . The common approach in these studies involves conducting separate MR analyses within distinct ethnic groups and subsequently comparing the nuances in the MR results between these groups.…”
Section: Introductionmentioning
confidence: 99%